A "Simplified" culotte technique using two dedicated bifurcation stents and additional angiographic stent enhancement to treat a complex bifurcation lesion in non‐ST segment elevation myocardial infarction with poor left ventricular function. Issue 6 (22nd January 2015) - Chan, Yu Ho; Stella, Pieter R.; Agostoni, Pierfrancesco
<x xml:space="preserve">Abstract</x> We present a case of a bifurcation lesion treated with two dedicated sirolimus eluting bifurcation stents, BiOSS Lim in the setting of non‐ST elevation myocardial infarction and poor left ventricular function. We demonstrate the feasibility of a new technique, a "simplified" culotte technique. The key differences of this new technique compared with conventional culotte are: better sizing of the stent due to the specific design of the stent with a larger proximal diameter and smaller distal diameter, direct stenting of the second stent without predilatation of the stent struts of the first deployed stent, and possibility to perform post‐dilatation directly with properly sized balloons without additional predilatation. © 2015 Wiley Periodicals, Inc.